Retrospective analysis of the impact of interruptions in radiation therapy on long term treatment outcomes for prostate adenocarcinoma - Hancharova, Katsiaryna; Batyan, Anatoly; Demeshko, Pavel; Damashnikava, Tatsiana (Journal of the Belarusian State University. Ecology, 2025)
The aim of the study was to analyze cancer-specific survival in patients who completed a course of radical radiotherapy for prostate adenocarcinoma, taking into account the duration of treatment interruptions as well as factors such as age, Gleason score, and PSA level. The retrospective study included data from 360 patients who underwent radiotherapy at the N.N. Alexandrov National Cancer Centre and the Brest Regional Oncology Dispensary (2008–2016). The median follow-up period was 60 months, and statistical analysis was conducted using Cox regression and Kaplan-Meier methods. The duration of treatment interruptions and the Gleason score had prognostic significance for cancer-specific survival (p < 0.05). Among patients with low and intermediate recurrence risk, interruptions of less than or more than 3 weeks did not affect survival (89,2 % versus 92,5 %, ρlogrank = 0,612). However, in high and very high-risk groups, the study demonstrated a significant impact of radiotherapy interruptions on patient survival (96,1 % versus 89,1 %, ρlogrank = 0,026). The obtained results emphasize the importance of strict adherence to radiation therapy schedules, especially for patients at high risk of disease recurrence. An individualized treatment approach, the use of modern radiation therapy techniques such as IMRT and VMAT, as well as compensation for treatment interruptions, may contribute to improved long-term clinical outcomes.
Keywords: radiation therapy; prostate adenocarcinoma; treatment interruptions; cancer-specific survival